A stable organic dye catholyte for long-life aqueous flow batteries. Issue 89 (20th October 2020) - Li, Hongbin; Fan, Hao; Ravivarma, Mahalingam; Hu, Bo; Feng, Yangyang; Song, Jiangxuan
Abstract : An exceptionally stable organic dye with high solubility was, for the first time, used as the catholyte for long-life aqueous flow batteries. Abstract : An organic dye, Basic blue 3 (BB3), was reported for the first time as a two-electron catholyte for aqueous redox flow batteries. The exceptional stability of BB3 enabled the full battery to achieve a high capacity retention of >99.991% per cycle during 1500 cycles.